Does corporate environmental performance affect corporate biodiversity reporting decision? The Finnish evidence - Dutta, Probal; Dutta, Anupam (Emerald, 2023)
Purpose This study aims to examine whether there exists any relationship between corporate biodiversity reporting decision (CBRD) and corporate environmental performance (CEP). Design/methodology/approach The primary sample contains 442 firm-year observations over a period of 13 years (2008–2020) for 34 listed Finnish companies. Based on both legitimacy theory and voluntary disclosure theory, 2 logit regression models are estimated to test the CBRD–CEP nexus. CBRD is a dichotomous variable. Three proxies for CEP, namely propensity to emit greenhouse gas (GHG), propensity to consume water and propensity to generate waste are employed. Findings This study finds that firms having higher propensity to consume water and generate waste are inclined to release biodiversity-related information. The findings support legitimacy theory suggesting that firms with inferior environmental performance may decide on reporting biodiversity information for legitimation purpose. Research limitations/implications The study uses Finnish data and hence, the results may lack in generalizability to other national contexts. Practical implications The results of this study should be valuable to policy makers for formulating mandatory biodiversity reporting standards to ensure disclosure of standard, extensive and authentic biodiversity-related information by companies. The results should also be valuable to corporate managers and eco-friendly investors. Originality/value Corporate biodiversity reporting (CBR) is an under-researched area of environmental accounting literature. Using the Finnish context, this paper extends the existing literature by investigating whether any association exists between CBRD and CEP, which has not been examined before.
Keywords: Ecosystem; Ecosystem services; Corporate biodiversity reporting; Corporate environmental performance; Finland; biodiversity; fi=Laskentatoimi ja rahoitus|en=Accounting and Finance|